Katandu: An Alternative Treatment And Traditional Health Maintenance Of The Muna Ethnic Group Through Bamboo Cupping (A Study In Tongkuno Selatan District, Muna Regency) - Agus Rihu; La Ode Marhini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the stages and processes of Katandu alternative therapy for treatment and traditional health maintenance of the Muna ethnic group through bamboo cupping. The informants of this research are cupping practitioners and patients who use cupping services determined by purposive sampling. The analysis technique used is qualitative descriptive analysis using the symbolic interaction theory by Herbert Blumer. The results of the research show that in the process of implementing alternative therapy for treatment and health maintenance through Katandu (bamboo cupping) on the Muna ethnic group (Study in Tongkuno Selatan District, Muna Regency) consists of: A. Preparation stage: a) Preparation of tools and equipment for sterilization and supporting tools such as: 1) Whetstone, 2) Cloth, 3) firewood and matches, b) Preparation of main tools and equipment during cupping ( katandu ) : 1) Bamboo cup (Lobu) as a tool for drawing out impure blood from the surface of the skin, 2) knife for cutting or incising the skin, 3) Water, 4) Stove, 5) Corn husk. c) Tools and equipment after cupping ( katandu ) consist of: 1) Ash, 2) Tissue. B. Cupping treatment stage includes: 1) Identifying complaints for cupping service users, 2) Determining points that will be the object of cupping, 3) Process of drawing out or removing impure blood. C. Conclusion stage includes: 1) dirty blood burial, 2) Katandu practitioner will pray for the patient's healing and health, 3) The patient will shake hands with the practitioner and give a certain amount of money as a token of gratitude for the service and healthcare provided.